The Use Of PCR To Diagnose Onychomycosis Caused By Non-Dermatophytic Molds - Bahram Ahmadi (پیاورد سلامت, 2015)
Background and Aim: Onychomycosis or nail fungus infection has an increasing prevalence with many effects on patients’ social life and mental health dermatophytes, yeasts and non-dermatophyte molds are among the best known agents of fungal infections of nails. The purpose of this study was to determine the prevalence of non-dermatophyte molds using morphological (direct examination and culture) and molecular (PCR) methods in patients referring to Medical Sciences Mycology Laboratory in Tehran, Iran.